A small secreted protein from Zymoseptoria tritici interacts with a wheat E3 ubiquitin ligase to promote disease. (23rd October 2020) - Karki, Sujit Jung; Reilly, Aisling; Zhou, Binbin; Mascarello, Maurizio; Burke, James; Doohan, Fiona; Douchkov, Dimitar; Schweizer, Patrick; Feechan, Angela
Abstract : A conserved secreted effector from the fungal pathogen Zymoseptoria tritici (ZtSSP2) promotes disease in wheat through an interaction with an E3 ubiquitin ligase. Abstract: Septoria tritici blotch (STB), caused by the ascomycete fungus Zymoseptoria tritici, is a major threat to wheat production worldwide. The Z. tritici genome encodes many small secreted proteins (ZtSSPs) that are likely to play a key role in the successful colonization of host tissues. However, few of these ZtSSPs have been functionally characterized for their role during infection. In this study, we identified and characterized a small, conserved cysteine-rich secreted effector from Z. tritici which has homologues in other plant pathogens in the Dothideomycetes . ZtSSP2 was expressed throughout Z. tritici infection in wheat, with the highest levels observed early during infection. A yeast two-hybrid assay revealed an interaction between ZtSSP2 and wheat E3 ubiquitin ligase (TaE3UBQ) in yeast, and this was further confirmed in planta using bimolecular fluorescence complementation and co-immunoprecipitation. Down-regulation of this wheat E3 ligase using virus-induced gene silencing increased the susceptibility of wheat to STB. Together, these results suggest that TaE3UBQ is likely to play a role in plant immunity to defend against Z. tritici.